Technological Lessons from the Fukushima Dai-Ichi Accident - Dion-Schwarz, Cynthia (RAND Corporation, 2016)
This study draws lessons regarding technological countermeasures to radioactive contamination caused by the Fukushima Dai-Ichi nuclear power plant accident. It focuses on contamination measurement, efforts to limit dispersal, decontamination, and storage of radioactive materials. The report analyzes technological successes and identifies capability gaps that could be redressed through novel technologies or improved use of existing technologies.